SOCIOLOGY OF WRITER AS THE BASIC ELEMENT TO COMPREHEND D.ZAWAWI IM-RON’S POEMS - Imron Wakhid Harits (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2015)
D.Zawawi Imron is one of an outstanding poet in Indonesia with his contemporary poems style. His life background, his culture, and his place where he lives are much affected to his works. This study is aimed to observe the influence of his life background to comprehend his works focusing on D. zawawi Imron poems. Because it is hard to comprehend and understand the messages and also the contents of his poems without observing his life background in Madura. His cultural identity as Madura people gives many contributions to his works. Not only giving the contribution, but it is also using as the main elements in all of his works, such as Dari Andulang ke Batang – Batang and Di Pintu Bandar. He always uses Madura culture and na-ture as the identity in his poems. The imagery, alliteration, simile, and other figurative languages refer to Madura culture and nature can be analyzed as the basic elements in D.Zawawi Imron’s poems. Thus, the sociology of writer is one of an appropriate approach to comprehend D.Zawawi Imron’s poems. Because by using sociology of writer, it can uncover the relationship between the writer’s/the poet’s life background, the creative process, and the content of the poems. Keywords: Sociology of writer, contemporary poems, Madura Identity